INTEGRITAS TOKOH HINDU DI DESA ADAT KAPAL KABUPATEN BADUNG: INTEGRITAS MORAL DAN SPIRITUAL TOKOH HINDU - Yulianti, Oggi; I Wayan Sugita; I Made Adi Brahman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
Hinduism figures in Bali are often regarded as role models, sources of inspiration in various religious activities, advisors in decision-making processes, as well as guides who lead the community toward a better path (gurus). This condition reflects the high expectations placed on religious figures. Moreover, individuals who are in the process of seeking a spiritual teacher are vulnerable to manipulation or even misguidance due to certain illegitimate religious figures (false gurus) who lack competence but have already begun guiding followers. This phenomenon underscores the critical importance of Hinduism leaders possessing high moral and spiritual integrity. This research aims to examine the forms of integrity among Hinduism figures in the Kapal Traditional Village, analyze their roles, and assess the implications for the development of Kapal Traditional Village in Badung Regency. The research is framed by three problem formulations: (1) What is the form of integrity demonstrated by Hinduism figures in the Kapal Traditional Village, Badung Regency? (2) What are the roles of Hinduism figures in the Kapal Traditional Village, Badung Regency? (3) What are the implications of the integrity of Hinduism figures in the Kapal Traditional Village for the progress of the village? This qualitative study uses data collected from interviews, observations, document analysis, and literature reviews, applying theories of religion, social role theory, and value theory. The study found that the attitudes and behaviors of Hinduism figures in Kapal Traditional Village, especially in terms of honesty and transparency, are exemplary. These figures consistently practice Hindu values in their daily lives, serve as role models for the local community, and are always willing to dedicate their time to offer guidance, provide explanations about rituals (upakara), and lead the community toward a closer relationship with God through meditation. The study also revealed that Hinduism figures in Kapal Traditional Village play psychological, religious-spiritual, and socio-cultural roles. Furthermore, the integrity of these figures aligns with several key values in Schwartz’s theory, particularly in the areas of Tradition, Conformity, Benevolence, Universalism, Self-Direction, Security, and Stimulation.